2003
DOI: 10.4049/jimmunol.171.11.6225
|View full text |Cite
|
Sign up to set email alerts
|

B-1 B Cells Mediate Required Early T Cell Recruitment to Elicit Protein-Induced Delayed-Type Hypersensitivity

Abstract: We define the initiation of elicited delayed-type hypersensitivity (DTH) as a series of processes leading to local extravascular recruitment of effector T cells. Responses thus have two sequential phases: 1) 2-h peaking initiation required for subsequent recruitment of T cells, and 2) the late classical 24-h component mediated by the recruited T cells. We analyzed DTH initiation to protein Ags induced by intradermal immunization without adjuvants. Ag-spceific initiating cells are present by 1 day in spleen and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
100
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(107 citation statements)
references
References 33 publications
6
100
0
1
Order By: Relevance
“…Since initiator B cells are IgM positive and our past studies have demonstrated that CS initiation is mediated by IgM Abs (3,4,7,19), Class-switch recombination resulting in isotype switching can be excluded, as can gene conversion which is not known to occur in mice (20). The formal possibility remains that some other, as yet unidentified, biological function of AID is required for the development of CS initiation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since initiator B cells are IgM positive and our past studies have demonstrated that CS initiation is mediated by IgM Abs (3,4,7,19), Class-switch recombination resulting in isotype switching can be excluded, as can gene conversion which is not known to occur in mice (20). The formal possibility remains that some other, as yet unidentified, biological function of AID is required for the development of CS initiation.…”
Section: Discussionmentioning
confidence: 99%
“…B cells are divided into several populations including B-2, B-1a and b, and marginal zone B cells, and recent evidence strongly suggests the existence of additional populations (10). Our previous studies identified the B cells responsible for CS initiation as a population of B-1 cells, based on their expression of CD11b in the PerC and CD5 in the spleen (1,2,4,7). However, the modern definition of B-1 cells has been expanded to include high expression of IgM and low expression of IgD, among others (see below) (11,12), which necessitates a re-evaluation of the identity of the B cell responsible for DTH/CS initiation.…”
Section: Identification Of Initiator B Cells a Novel Subset Of Activmentioning
confidence: 99%
See 1 more Smart Citation
“…In the induction phase, the hapten penetrates the skin barrier, which activates dendritic cells that migrate to draining lymph nodes with priming of naïve T cells and later activation of hapten-specific T cells [45][46][47][48]. The elicitation phase normally begins with renewed exposure to the hapten, when the hapten is presented to hapten-specific T cells by allergen-presenting cells with the result of local cytokine and chemokine release [45,49]. These mediators both have proinflammatory responses and recruit other inflammatory cells, which makes the skin develop acute dermatitis with erythema, edema, infiltration, and vesicles.…”
Section: Pathogenesismentioning
confidence: 99%
“…Gnotobiotic immunologically-active molecule mutant or knockout mice are commonly used in studies on immunological mechanisms and animal models of human autoimmune diseases (e.g., SABELKO-DOWNES et al 2000;MACPHERSON et al 2001;PAUL et al 2003;SZCZEPANIK et al 2003). In the course of a routine histological examination of the cerebra of pathogen-free autoimmunity prone and immunological molecule knockout mice, moderate to severe pathological changes in their cerebra were observed.…”
mentioning
confidence: 99%